Analisis Dugaan Transaksi Mencurigakan Untuk Kepentingan Ilegal Pada Nasabah Bri Kcp Simpang Tiga Kota Pekanbaru - Endang Sri Wahyuningsih; Siti Rodiah (Universitas Teuku Umar, 2023)
This study aims to determine the settlement of suspected suspicious transactions related to online gambling at BRI KCP Simpang Tiga. The problem studied is resolving customers suspected of carrying out suspicious transactions. Data were collected by interview and document recording; and analyzed using case study analysis with a qualitative approach. The results of the research show (1) customers provide different information to the bank; (2) customers who are suspected of making suspicious transactions, their account card must be immediately blocked so that irresponsible parties cannot misuse them; (3) if the accounts are not immediately closed or blocked, more people will be deceived; (4) before the account is blocked, the bank must confirm with the customer by visiting; and (5) the customer makes a statement. If something similar happens, the customer cannot open a new account at BRI. To avoid fraud related to online gambling transactions, customers should not easily give their accounts or personal data to others. To avoid being misused by irresponsible parties, customers must maintain data confidentiality, such as not providing usernames, passwords and OTP codes to any party, including family, friends, and the bank.